Nosocomial diarrhea: Trauma center health professionals’ knowledge and practice - Benites Nemetz, Kellen; Müller Pacheco, Pauline; Macedo Cuervo, Maria Rita (O Mundo da Saúde, 2018)
The occurrence of diarrhea in critically ill patients is frequent, regardless of the cause of initial admission to the Intensive Care Unit (ICU). Nosocomial diarrhea may have important clinical and economic implications. It’s proper handling depends on correct diagnosis and recording. The aim of the present study was to verify the knowledge concerning the concept of diarrhea of health professionals working in the ICUs of a Trauma Center. This is a cross-sectional study conducted in July 2016 with 89 professionals, those being 18 nurses, 41 nurse technicians and 30 nursing assistants working in ICUs. Workers on leave or vacation were excluded. Participants answered a self-administered questionnaire containing 12 objective questions. Descriptive statistical analyses of absolute and relative frequencies were performed using SPSS 21.0 software. Most of the employees were between 51 and 60 years old and worked mostly at night. Only 60% of health professionals correctly identified diarrhea and 31% of professionals do not consider the number of evacuations to classify diarrhea. A third reported completing the full medical record of bowel movements in the chart set in the patients’ bed and (3%) received training on the subject within the institution. It was observed that the knowledge of these professionals was similar to those of the other studies, but still not satisfactory. The situation represents an important factor for the super- or under-diagnosis of this disease and consequent complications, arguing for the potential that continuing education has to contribute for clinical practice qualification.